Pengaruh Bias Kognitif terhadap Pengambilan Keputusan Investasi di Platform Digital pada Generasi Y dan Z - Isywara, Aristi Prita; Nimas Tasia, Winda Rein; Ramadhan, Fadilatur; Prastiwi, Arum (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: This study aims to empirically prove the effect of cognitive biases on investment decision making on digital platforms in Y and Z generations in Malang City (East Java). Measurement of cognitive bias considers three things: cognitive dissonance bias, overconfidence, and illusion of control. Method: This study uses a quantitative descriptive approach. The sampling method used is convenience sampling with the criteria of the age range 18-35 years. This study used multiple regression tests to see the effect of independent and dependent variables, and uses the SPSS 25 analysis tool. Results: The results of this study indicate that cognitive dissonance bias and overconfidence have a significant negative effect on investment decisions, and illusion of control has a significant positive effect on investment decisions. Implications: This research can provide information related to cognitive biases in making investment-related decisions, especially for investors so that they are not wrong in making investment decisions. Novelty: This study uses a sample of Y and Z generations in Malang City, and looks at how cognitive biases are affected through digital investment platforms.